DRAW THE MONSTER: PROMOTING STUDENTS’ INTERACTION THROUGH COLLABORATIVE WORK - Yulieda Hermaniar; Agustina Lestary (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2018)
AbstractElite English Course Banjarmasin is a private English course using games and related traditional activities in the lesson. One of the activity used is drawing. In 90 minutes lesson, various technique are used in every stage of the lesson which involve drawing activity. The drawing activities is promoting not only the students involvement but also togetherness, as it is seen when students are drawing and coloring the monster on activity book. Therefore, the study is conducted to describe how the drawing activity promote meaningful learning and interaction through grouping system in drawing activities. Under the descriptive qualitative method, the discussion of the study covers the detail stages implemented in the classroom, the various activity of drawing, and the related theories supporting or contrasting the findings. The study is expected to give beneficial contribution for teachers who have similar characteristics with Elite English Course Banjarmasin as well as education practitioners as references for further research.